PENGARUH MEDIA SOSIAL TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS VII DI MTS NEGERI 1 KUANTAN SINGINGI - Reni Oknalita; Supentri Supentri; Indra Primahardani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research is motivated by phenomena that arise based on observations on learning period using online and offline systems which is social media is used as learning medium. This regarding because many students are access social media in the school environment. So that the time that should be used for learning is only used to play social media, imitating bad morals, delaying study time, lazy to do activities, this causes learning outcomes being decrease. Based on pre-research results, the research shows that students play social media for about ± 20 hours even up to 24 hours / day because social media has become a necessity in everyday life. This study aims to determine The influence of Social Media on the Learning Outcomes of Seventh Grade Students at MTS Negeri 1 Kuantan Singingi. With a sample of 40 students. This research method uses quantitative descriptive analysis, the data is analyzed using simple linear regression. Based on the results of research on The influence of Social Media on the Learning Outcomes of Seventh Grade Students at MTS Negeri 1 Kuantan Singingi, it can be concluded that: There is a significant influence between social media and learning outcomes. So the hypothesis in this study is accepted, based on the coefficient of determination test (R square) of 0.374, which implies that the influence of the independent variable (social media) on the dependent variable (learning outcomes) is 61.2%.Key Words: Influence, Social Media, Students, And Learning Outcomes